2017
DOI: 10.1287/orsc.2017.1154
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Organizational Atypicality on Reference Group Selection and Performance Evaluation

Abstract: Recent research shows that audiences sometimes respond to organizational performance in ways that seem anomalous according to prior theory. In this paper we propose that variations in the extent to which an organization conforms to the norms and expectations of a known organizational category can affect the way evaluators construct reference groups, and subsequently shape their responses to organizational performance. In an experiment on investing in and evaluating the performance of a certain kind of financia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 60 publications
1
28
0
Order By: Relevance
“…Another series of studies found that atypical firms receive higher rewards for good performance and less punishment for poor performance (Smith 2011) in part because their performance is evaluated against a different benchmark, making good performance appear better and poor performance appear merely mediocre (Smith and Chae 2017). Meanwhile, firms perceived as presenting a higher liability risk because they were targeted by shareholder activists experienced a decrease in their market value despite having the same environmental performance as their peers (Vasi and King 2012).…”
Section: Social Performance Ratings and Firm Preferencesmentioning
confidence: 99%
“…Another series of studies found that atypical firms receive higher rewards for good performance and less punishment for poor performance (Smith 2011) in part because their performance is evaluated against a different benchmark, making good performance appear better and poor performance appear merely mediocre (Smith and Chae 2017). Meanwhile, firms perceived as presenting a higher liability risk because they were targeted by shareholder activists experienced a decrease in their market value despite having the same environmental performance as their peers (Vasi and King 2012).…”
Section: Social Performance Ratings and Firm Preferencesmentioning
confidence: 99%
“…Research on social comparisons suggests that there should be variation in the tendency to benchmark against similar others (Festinger 1954, Audia et al 2016, Smith and Chae 2017 there are differences in incentives and opportunities to select dissimilar comparison peers. Building on this research, we propose that weak performance on the metrics that affect CEO compensation creates an incentive to bias the peer group upward, while ambiguity in the set of firms most similar to the focal firm creates an opportunity to do so.…”
Section: Peer Group Bias: Incentives and Opportunitiesmentioning
confidence: 99%
“…Compensation benchmarking involves the assembly of a group of peer firms that serves as a lens through which CEO compensation can be evaluated (Barsalou 1983, Podolny 2001, Smith and Chae 2017. The Securities and Exchange Commission (SEC) made disclosure of these peer groups mandatory in 2007.…”
Section: Introductionmentioning
confidence: 99%
“…A potential explanation for this trend draws from the way in which companies benchmark the compensation of their CEOs (DiPrete, Eirich, and Pittinsky 2010, Faulkender and Yang 2013, Albuquerque, De Franco, and Verdi 2013, Pittinsky and DiPrete 2013. Compensation benchmarking involves the assembly of a group of peer firms that serves as a lens through which CEO compensation can be evaluated (Barsalou 1983, Podolny 2001, Smith and Chae 2017. The Securities and Exchange Commission (SEC) made disclosure of these peer groups mandatory in 2007.…”
Section: Introductionmentioning
confidence: 99%
“…We then examine the conditions under which peer group bias should be most pronounced. We draw from research on social comparisons (Audia et al 2016, Smith andChae 2017) and predict that peer group bias should increase when the firm fails to meet its financial targets and when firms can exercise benchmarking discretion as a result of ambiguity about the set of firms that are most similar to the focal firm, i.e. its "natural" or "counterfactual" peers.…”
Section: Introductionmentioning
confidence: 99%